2009
DOI: 10.1051/0004-6361/200810709
|View full text |Cite
|
Sign up to set email alerts
|

The origin of intrinsic variability of intraday variable sources

Abstract: Intraday variability (IDV) describes flux-density variations in the radio regime on timescales of a day and less. The origin of such variations has been attributed to both source intrinsic and extrinsic mechanisms. While there is growing evidence that faster fluxdensity variations (on the order of hours to minutes) are caused by refractive interstellar scattering, extrinsic mechanisms alone still fail to explain all the observations. In particular, in the blazar S5 0716+714, correlated variations at frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…We conclude, remarking that if the inner parts of the accretion disk contain a warp or precess faster than the precession of the outer part, this will produce a very small perturbation that will produce a day-to-month variability of the core flux (Roland et al 2009). Solutions 1 and 5 are excluded because they have γ c > 30 .…”
Section: Discussionmentioning
confidence: 98%
“…We conclude, remarking that if the inner parts of the accretion disk contain a warp or precess faster than the precession of the outer part, this will produce a very small perturbation that will produce a day-to-month variability of the core flux (Roland et al 2009). Solutions 1 and 5 are excluded because they have γ c > 30 .…”
Section: Discussionmentioning
confidence: 98%
“…However, in the case of S5 0716+714, correlated variations at frequencies in the radio and the optical regimes indicate an intrinsic component to the variability. Roland et al (2009) found that the formation and the rotation of a warp in the inner part of the accretion disk produce a small perturbation of the relativistic beam and consequently a variation in the viewing angle and in the beamed synchrotron emission explaining IDV variations.…”
Section: Astrophysical Phenomena Involved In the Optical Flux Variatimentioning
confidence: 97%
“…Usually, for the IDV light curve of blazars there is no significant pattern and period. Roland et al (2009) proposed that the formation and the rotation of a warp in the inner part of the accretion disk can lead to some perturbations of the beam that finally produce the observed IDV.…”
Section: Introductionmentioning
confidence: 99%